Mechanism of the transition from external oxide scales to internal oxidation for Fe-Si alloys in the atmosphere with very low oxygen partial pressure. (29th March 2019) - Zhang, Hao-Yu; Liu, Xiao-Jiang; Wang, Chuan; Zhou, Ge; Chen, Li-Jia
Abstract: For silicon steels surface defect is rather common as compared with that of the plain carbon steels due to the incorporation of Si. Researcher have studied oxidation behavior of silicon steels in reheating stage a lot while that of cooling stage after coiling was seldom discussed. In the present work, hot rolled Fe-Si alloys containing 0.75 and 1.5 wt% Si, which possessed the external oxide scales in the thickness of approximately 10 μ m, were used to study the transition behavior from external oxide scales to internal oxidation. The hot rolled specimens were heat-treated at 600 °C–1150 °C in the atmosphere of pure Argon at 1 atm for 2 h. It has been observed that internal oxidation zone (IOZ) was formed in the temperature range from 700 to 1150 °C in Fe-0.75Si alloy, while the IOZ was formed in the temperature range from 1000 to 1150 °C in Fe-1.5Si alloy. By using the Wagner theory for internal oxidation kinetics and taking the equilibrium oxygen partial pressure for FeO into account, the internal oxidation depth has been calculated. After modification with reheating and cooling processes, the calculated values are in good agreement with the measured values. For Fe-0.75Si alloy, after the heat treatment at 800 °C, the calculated value after modification was obtained to be about 5.7 μ m, close to the measured value of 6.1 μ m, which indicates that the decomposition of oxide scale should be the main driving force for the growth of internal oxidation. In the atmosphere of pure Ar at high temperatures, Fe3 O4 transformed to FeO, which is relatively thermodynamically stable. After the transformation, FeO may be decomposed to Fe and O 2- due to the depletion of oxygen at the interface between oxide scale and steel substrate. O 2− ions are dissolved and diffused in the steel substrate, which react with Si to form internal oxides of SiO2 .